Role of bokashi fertilizer in increasing growth and yield components of groundnut on marginal dry land in southeast Sulawesi - Rahni, Nini Mila; Hervina, Wa Ode; Alam, Syamsu (Jurnal AGRO, 2024)
The low growth and production of groundnuts in Southeast Sulawesi are caused by land dominated by marginal dry land and low soil fertility. One of the efforts to overcome these problems is converting secondary vegetation into bokashi fertilizer, effectively improving soil's physical, chemical, and biological properties on marginal land. This study aims to determine the effect of bokashi fertilizer on the growth and yield of several ecotypes of groundnut plants on marginal dry land in South Konawe. This research was conducted in Baito-South Konawe. Laboratory analysis was conducted at the Agrotechnology Laboratory, Faculty of Agriculture, Halu Oleo University, Kendari. The design used a randomized block design with a factorial pattern of two factors, the first factor was groundnut ecotype, and the second factor was bokashi fertilizer. Parameters observed were relative growth rate, leaf area index, net assimilation rate, productive branches, number of young pods, seed weight per plant, the weight of 100 seeds, and plant production. The results showed that there was an interaction effect between the local groundnut ecotype Muna and bokashi fertilizer on the relative growth rate, leaf area index, net assimilation rate at 56 DAP, productive branches, number of young pods, seed weight per plant, the weight of 100 seeds and production. The application of bokashi fertilizer 15 t ha-1 showed the best response of groundnut plants to the ecotypes of Wadaga, Parigi, and Lasehao.Rendahnya pertumbuhan dan produksi tanaman kacang tanah di Sulawesi Tenggara disebabkan oleh lahan yang didominasi lahan kering marginal dengan kesuburan tanah yang rendah. Salah satu upaya untuk mengatasi permasalahan tersebut adalah dengan pemanfaatan limbah pertanian menjadi pupuk bokashi yang efektif memperbaiki sifat fisika, kimia dan biologi tanah. Penelitian ini bertujuan untuk menganalisis pengaruh pupuk bokashi terhadap pertumbuhan dan hasil beberapa ekotipe tanaman kacang tanah pada lahan kering marginal. Penelitian lapangan dilaksanakan di Kecamatan Baito, Kabupaten Konawe Selatan. Penelitian laboratorium dilaksanakan di Laboratorium Agroteknologi Universitas Halu Oleo, Kendari. Desain penelitian menggunakan rancangan acak kelompok dengan dua faktor yaitu pertama faktor ekotipe kacang tanah dan kedua faktor dosis pupuk bokashi. Parameter yang diamati yaitu laju tumbuh relatif, indeks luas daun, laju asimilasi bersih, cabang produktif, jumlah polong muda, bobot biji per tanaman, dan bobot 100 biji tanaman. Hasil penelitian menunjukkan bahwa terdapat interaksi antara ekotipe kacang tanah lokal Muna dan pupuk bokashi dalam mempengaruhi laju tumbuh relatif, indeks luas daun, laju asimilasi bersih pada umur 56 HST, cabang produktif, jumlah polong muda, bobot biji per tanaman, dan bobot 100 biji. Pemberian pupuk bokashi 15 t ha-1 menunjukkan respon tanaman kacang tanah terbaik pada ekotipe Wadaga, Parigi dan Lasehao.